PEMANFAATAN SILINDER LIMBAH TES BETON SEBAGAI DINDING PENAHAN TANAH TIPE GRAVITASI - Dimas Prasetyo Muhammad, Gerard Aponno, Suselo Utoyo (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
The utilization of concrete-test-cylindrical waste was few due to it’s tendency to roll over when being stacked and the stacked form was not uniform like cubed waste. That is why the writer wants to use the cylindrical waste as a material of gravity-typed retaining wall.The purpose of this study is to find out the stability, cost, and implemention method of cylindrical waste as a material such retaining wall.The stability analysis of retaining wall made from cylindrical concrete was compared to commonly stoned retaining wall through trial and error method. The next step was to make the construction of retaining wall made from cylindrical concrete and stone to see the implemetion method and cost needed per m3. Stability analysis results in cylindrical concrete retaining wall safe from rolling, sliding, and reaction of foundation soil. Compared to stoned retaining wall of 3,00 m tall and 1,70 m long, it has safety factor (SF) Fgl = 2.13, Fgs = 2,37, and qumax = 4,07 ton/m2 which means it is close to the FS of stoned retaining wall Fgl = 2.18, Fgs = 2,39, and qumax = 9,89 ton/m2 ; at IDR 1.012.093,74 per m3 which means it is IDR 389.553 more expensive ; and it is of horizontal arragement.Keywords: retaining wall, concrete-test cylinder, stability, cost estimate, horizontal arrangement.